2007
DOI: 10.1063/1.2806992
|View full text |Cite
|
Sign up to set email alerts
|

The vibrational spectra of protonated water clusters: A benchmark for self-consistent-charge density-functional tight binding

Abstract: The vibrational spectra of protonated water clusters: A benchmark for selfconsistent-charge density-functional tight binding AbstractProton transfers are involved in many chemical processes in solution and in biological systems. Although water molecules have been known to transiently facilitate proton transfers, the possibility that water molecules may serve as the "storage site" for proton in biological systems has only been raised in recent years. To characterize the structural and possibly the dynamic natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 54 publications
3
63
0
2
Order By: Relevance
“…Various applications have shown that SCC-DFTB is able to reproduce DFT results with sufficient accuracy in many systems (34,35). For the present study, the ability of SCC-DFTB to reproduce strongly hydrogen bonded structures and proton affinities as well as the qualitative spectral features of various water clusters have been shown in recent studies (36,37) (also see SI for additional benchmarks).…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Various applications have shown that SCC-DFTB is able to reproduce DFT results with sufficient accuracy in many systems (34,35). For the present study, the ability of SCC-DFTB to reproduce strongly hydrogen bonded structures and proton affinities as well as the qualitative spectral features of various water clusters have been shown in recent studies (36,37) (also see SI for additional benchmarks).…”
Section: Methodsmentioning
confidence: 72%
“…The IR spectrum for the QM region is computed by the Fourier transform of the dipole autocorrelation function collected from SCC-DFTB/MM molecular dynamics trajectories; multiple independent simulations are carried out for statistical significance. The nuclear quantum effect on the computed IR spectra is approximated with a harmonic quantum correction factor as done in the recent study of water clusters (37). See SI for additional technical details and discussions.…”
Section: Methodsmentioning
confidence: 99%
“…The "intermolecular proton bond" explains the short distance between the two Glu sidechains as observed in several crystal structures. Importantly, this Glu-pair model qualitatively captures the continuum feature in the IR spectra near 18002000 cm 1 (Figure 3(c)); similar to the case of protonated water cluster [82], MD simulations are essential for capturing the proper continuum feature. Moreover, the connection between the proton de-localization and the continuum band was shown explicitly by a simulation in which only one of the Glu sidechains was treated as QM, thus abolishing both delocalization of the stored proton and the continuum band.…”
Section: Involvement Of An Unusual Titratable Group As Proton Loadingmentioning
confidence: 88%
“…полос в рамках кластерной схемы строения воды (Н 2 О) n в соответствии с литературными данными [33,34]. Особенность спектров КР в диапазоне 4000−3000 сm −1 заключалась в значительном различии интенсивностей (I) полос для компонент излучения, рассеянного в ортогональных направлениях (I z z и I z y ) и (I y y и I y z ) соответственно вдоль и поперек c-каналов об-разца (рис.…”
Section: результаты экспериментаunclassified
“…Полосы в области 4000−3750 cm −1 относятся к антисимметричным колебаниям свободных гидроксилов [34,35]. Диффузная полоса 2960−2900 сm [37][38][39][40].…”
Section: результаты экспериментаunclassified